Isochronous control of a virtual synchronous generator using inertia and excitation emulations with restoration control in a standalone microgrid. Issue 6 (19th November 2020) - Samanta, Soumya; Mishra, Jyoti Prakash; Roy, Binoy Krishna
Abstract : In this study, virtual excitation emulation (VEE) is proposed along with the virtual inertia emulation (VIE) for a virtual synchronous generator (VSG) in a standalone microgrid to improve the AC voltage and frequency profile through the control of power electronic DC–AC converter in the microgrid. The VIE emulates the inertia and damping characteristics of a synchronous generator by mimicking the swing equation. The VEE is proposed to emulate the behaviour of the field circuit and exciter system of a synchronous generator. In addition, a restoration control is also added with the inertia and excitation emulation to restore the magnitude and frequency of the output voltage at the rated value and achieve isochronous control. A linearised small‐signal model of the VSG with the proposed control technique is also presented to analyse the system stability and design the control parameters. The standalone microgrid is simulated in MATLAB/Simulink environment to show the effectiveness of the proposed control technique. From the simulation results, it is reflected that the proposed control technique improves the voltage and frequency response during transient and steady‐state including the frequency nadir of the microgrid.